Impact of land use/land cover changes on surface water and soil-sediment export in the urbanized Akaki River catchment, Awash Basin, Ethiopia - Mekuria Argaw; Hamere Yohannes (Journal of Hydrology: Regional Studies, 2024)
The Akaki River catchment is undergoing rapid urbanization and substantial deforestation, leading to a decline in its hydrological conditions. Investigating how changes in land use and land cover (LULC) affect the hydrological cycle in urbanized catchments like the Akaki River in the Awash Basin is a priority in natural resource utilization and management. By analyzing satellite images and using the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) and Partial Least Square Regression (PLSR) models, this study examined the hydrological responses such as water yield (WY), sediment export (SE) and soil loss (SL) to the prevailing LULC changes in the catchments. The results showed an increasing trend of risks in surface runoff and sediment export from the catchments in the past three decades. The Analysis of Variance (ANOVA) test results showed significant variations in WY, SE, and SL across LULC types throughout the study period. The variables WY, SE, and SL increased by 35.25%, 8.11%, and 10.71%, respectively. The magnitude of change in SE, SL, and WY over the study period was substantially influenced by not only the change in LULC but also by the dynamics. Most importantly, settlements and farmlands were the main factors that influenced the hydrological components. These two LULC types attained greater variable importance for projection (VIP) and parameter weight (w) values of 1.31 and 0.61 for settlement and 1.19 and 0.56 for farmlands, respectively. The results of the study underlined the importance of regulating the rapidly changing LULC change and implementing conservation measures in order to attain a sustained hydrological and ecological balance in the Akaki River catchments,